Brown Adipose Tissue Energy Metabolism in Humans - Carpentier, André C.; Blondin, Denis P.; Virtanen, Kirsi A.; Richard, Denis; Haman, François; Turcotte, Éric E. (Frontiers in Endocrinology, 2018)
The demonstration of metabolically active brown adipose tissue (BAT) in humans primarily using positron emission tomography coupled to computed tomography (PET/CT) with the glucose tracer 18-fluorodeoxyglucose (18FDG) has renewed the interest of the scientific and medical community in the possible role of BAT as a target for the prevention and treatment of obesity and type 2 diabetes (T2D). Here, we offer a comprehensive review of BAT energy metabolism in humans. Considerable advances in methods to measure BAT energy metabolism, including nonesterified fatty acids (NEFA), chylomicron-triglycerides (TG), oxygen, Krebs cycle rate, and intracellular TG have led to very good quantification of energy substrate metabolism per volume of active BAT in vivo. These studies have also shown that intracellular TG are likely the primary energy source of BAT upon activation by cold. Current estimates of BAT’s contribution to energy expenditure range at the lower end of what would be potentially clinically relevant if chronically sustained. Yet, 18FDG PET/CT remains the gold-standard defining method to quantify total BAT volume of activity, used to calculate BAT’s total energy expenditure. Unfortunately, BAT glucose metabolism better reflects BAT’s insulin sensitivity and blood flow. It is now clear that most glucose taken up by BAT does not fuel mitochondrial oxidative metabolism and that BAT glucose uptake can therefore be disconnected from thermogenesis. Furthermore, BAT thermogenesis is efficiently recruited upon repeated cold exposure, doubling to tripling its total oxidative capacity, with reciprocal reduction of muscle thermogenesis. Recent data suggest that total BAT volume may be much larger than the typically observed 50 to 150 ml with 18FDG PET/CT. Therefore, the current estimates of total BAT thermogenesis, largely relying on total BAT volume using 18FDG PET/CT, may underestimate the true contribution of BAT to total energy expenditure. Quantification of the contribution of BAT to energy expenditure begs for the development of more integrated whole body in vivo methods.